2014
DOI: 10.5713/ajas.2014.14170
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relationships of Carcass Traits with Retail Cut Productivity of Hanwoo Cattle

Abstract: This study aimed to estimate genetic correlation between carcass grading and retail productivity traits and to estimate the correlated response on retail productivity traits through selection for carcass grading traits in order to assess the efficacy of indirect selection. Genetic parameters were estimated with the data from 4240 Hanwoo steers using mixed models, and phenotypes included carcass weight (CWT), back fat thickness (BFT), eye muscle area (EMA), marbling (MAR), and estimated lean yield percentage (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…The low contribution of MAR in predicting %RC and %FAT in this study could be due to a low correlation between MAR and %RC and %FAT in Hanwoo steer carcasses. Koh et al (2014) reported a small and positive phenotypic correlation between MAR and %RC and %FAT in Hanwoo steer data (r = +0.04 and +0.07, respectively), of which similar and positive correlation coefficients of +0.02 and +0.03 were estimated in the preliminary analyses of this study (data not shown).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The low contribution of MAR in predicting %RC and %FAT in this study could be due to a low correlation between MAR and %RC and %FAT in Hanwoo steer carcasses. Koh et al (2014) reported a small and positive phenotypic correlation between MAR and %RC and %FAT in Hanwoo steer data (r = +0.04 and +0.07, respectively), of which similar and positive correlation coefficients of +0.02 and +0.03 were estimated in the preliminary analyses of this study (data not shown).…”
Section: Discussionsupporting
confidence: 80%
“…The number of animals per slaughter year were 1,162, 1,227, 1,857, 1,450, 1,168, and 1,043 for year 2009, 2010, 2011, 2012, 2013, and 2014, respectively, and mean age in month was 31.97±3.22. The feeding and management of the steers has been explained by Koh et al (2014) .…”
Section: Methodsmentioning
confidence: 99%
“…It was higher than the heritability estimate of 0.39 in CW and lower than the heritability estimate of 0.62 in MS reported by Sun et al [19] in Hanwoo. The heritability of CW from this study was estimated higher than that of the study using performance testing re-cords of Hanwoo young bulls (0.37) [20], and using the data from Hanwoo steers [21]. Table 8 shows the genetic and phenotypic correlations between traits studied.…”
Section: Monthly Performance Of Steers In Carcass Traitsmentioning
confidence: 67%
“…The Guidelines of Uniform Beef Improvement Programs ( BIF, 2010 ) have facilitated the use of records to improve beef productivity, and the National Beef Quality Audit ( Moore et al, 2012 ) has provided industry guidelines for quality conformance in the US. Numerous studies have also been conducted to investigate the carcass traits of various cattle breeds and provide genetic characteristics of the breeds ( Koots et al, 1994 ; Choy et al, 2005 ; Ríos-Utrera, 2005 ; Casas et al, 2010 ; Park et al, 2013 ; Koh et al, 2014 ). Studies on estimation of genetic parameters with few carcass traits (3 or 5 traits) were carried out for probing better estimation in Hanwoo ( Lee, 2004 ; Roh et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%